1989
DOI: 10.1111/j.1752-7325.1989.tb02017.x
|View full text |Cite
|
Sign up to set email alerts
|

How Effective is Oral Hygiene Instruction? Results after 6 and 24 Weeks

Abstract: We studied the clinical effectiveness of oral hygiene instruction given to 71 "high" plaque patients in 19 Washington State dental practices to determine the extent of plaque reduction. Patients were examined prior to instruction and prophylaxis. Therapist instructions were tape-recorded and content analyzed, and therapists' expectations were scored. Patients were surveyed as to oral health behaviors and general health habit characteristics. Only 20 of 71 (28%) initially "high" plaque patients had reduced mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…It has been proposed that the main cause of insufficient oral hygiene in the general population is a result of too short brushing time 18 . However, changing the behavior in this regard seems to be very difficult 19 . The commonly recommended toothbrushing time varies from 120 seconds (United States) and 180 seconds (Europe).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the main cause of insufficient oral hygiene in the general population is a result of too short brushing time 18 . However, changing the behavior in this regard seems to be very difficult 19 . The commonly recommended toothbrushing time varies from 120 seconds (United States) and 180 seconds (Europe).…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study supports previous studies that showed statistically significant improvement in VSC levels after non-surgical periodontal therapy. [1022] Although it was reported that the expected improvement in oral hygiene after oral hygiene instruction may be overestimated,[23] another study reported highly significant improvements in oral health after dental education and oral hygiene instruction. [24]…”
Section: Discussionmentioning
confidence: 99%
“…Though the cause of this phenomena is poorly understood, many suggestions have been proposed [5, 7–9, 9, 2630]. It is possible that, for example, as a child ages and his/her level of skill improves, he or she may develop effective tooth brushing skills [26, 27]; however, once ineffective skills are developed, it may be difficult for an adult to alter his or her established oral hygiene practices—i.e., an adult with an ingrained habit may have less learning plasticity as compared to a child or adolescent [31]. Furthermore, to date, to our knowledge, few investigators have viewed tooth brushing as a routine habit through a prism of procedural-implicit memory.…”
Section: Working Hypothesismentioning
confidence: 99%